Identificação de peptídeos sintéticos ligantes à imunoglobulinas G de pacientes com neurocisticercose por Phage display - Ribeiro, Vanessa da Silva (2009)
Neurocysticercosis (NC), presence of Taenia solium metacestodes in the central nervous system is the most serious form of cysticercosis and is the cause of epilepsy in countries under development. The improvement of immunodiagnostic tests which use recombinant antigens is importance because of the difficulty of obtaining parasites from naturally infected pigs for the preparation of metacestodes T. solium metacestodes crude antigen. The aim of this study was to select phagotopes by phage display peptide library specific to IgG present in serum samples from patients with NC and confirm the immunoreactivity from the selected phagetopes in the ELISA test for the diagnosis of human neurocysticercosis in serum samples. We used in the selection procedure a phage display peptide library in a selection strategy against the immunoglobulins (IgG) purified from serum samples positively diagnosed for NC, other parasitoses and apparently health individuals. The DNA sequences corresponding to the inserts of the selected phage clones were sequenced, translated and analyzed by bioinformatics. ELISA tests were performed with the ten phagetopes selected against the three groups of patients (NC, other parasitoses and healthy). The binding specificities of the recombinant phages to the pool of serum samples were analyzed by competitive ELISA. Peptides showed significant similarities with important proteins from T. solium. All phagetopes presented satisfactory sensitivities and specificities in the ELISA test, varying from 52.5% to 100% and 86.3% to 100%, respectively. Some phagetopes did not reacted with serum samples from patients infected with Echinococcus granulosus, what is an advance since this cross reaction is very commonly reported. The recognition data indicated that the selected peptides could indeed mimic the epitopes on T. solium and bind specifically to the pool of serum with NC. We concluded that the identified phage clones displayed specific peptides to NC, and are potential biomarkers for NC diagnosis in serum samples.